Productivity analysis of selected wind turbines in Poland - Wichliński, Michał; Kubus, Norbert (Instal, 2024)
Wind energy is a very important component of the Polish energy mix. As we move away from conventional sources, wind farms and solar energy will have to take on the burden of electricity production. However, the operation of wind turbines depends on temporary weather conditions, i.e. wind speed. This article presents an analysis of the productivity of four selected wind turbines located in four different locations. The amount of energy produced by individual turbines during the year varied significantly. A clearly visible decrease in production in the summer months (June-September) and an increase in production in the remaining months, especially from October to December, is visible. Wind speeds above 10 m/s, at which the turbines operated, did not exceed 11% during the year, for about 17% of the year wind speeds were below 4 m/s. In calm weather, turbines also need electricity to power internal systems, the analyzed turbines had to be powered from outside for about 13% of the time during the year.
Keywords: wind energy; wind turbines; energy production; wind speed